Dry Sliding Wear Behaviour Of Thixoformed Hypoeutectic AL–SI–CU Alloy With Different Amounts Of Magnesium - Alhawari, Khalid Salim; Omar, Mohd Zaidi; Ghazali, Mariyam Jameelah; Salleh, Mohd Shukor (Taylor & Francis Online, 2016)
-